Thoracic Epidural Teratoma: Case Report and Review of the Literature - Jennifer L. Quon; Ryan A. Grant; Anita J. Huttner; Charles C. Duncan (SAGE Publishing, 2014)
Purpose Spinal teratomas comprise a rare subset of spinal cord tumors, and here, we describe an even rarer childhood thoracic extradural-intracanalicular teratoma. The clinical presentation, management, and pathophysiology of these tumors are reviewed to promote recognition and guide treatment of these lesions. Methods We report the case of a 21-month-old boy who presented with marked spasticity, as well as failure to ambulate and meet motor milestones. Additionally, we provide a literature review of spinal teratomas, including their clinical presentation, work-up, pathophysiology, and underlying genetics. Results An MRI of the spine revealed a large dorsal epidural tumor extending from T3 to T10 with heterogeneous contrast enhancement and severe spinal cord compression. The tumor was resected revealing a cystic mass with tissue resembling hair, muscle, as well as cartilage; pathology confirmed the diagnosis of teratoma. Gross total resection was achieved, and the child eventually gained ambulatory function. Conclusions Given that spinal teratomas are rare entities that can present with significant neurologic compromise, they must remain on clinicians' differentials. Unfortunately, the exact origin of these tumors remains inconclusive and requires further investigation.